2013
DOI: 10.2298/vsp1304396v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment with omega-3 polyunsaturated fatty acids (PUFAs) on hematological parameters and platelets aggregation in patients during elective coronary artery bypass grafting

Abstract: This prospective, randomized, placebo-controlled, single-center trial was performed on parallel groups. The patients (n = 40) undergoing elective CABG were randomized receivin preoperative intravenous omega-3 PUFAs (Omegaven 10%) infusion (the PUFAs group) or the same volume of 0.9% saline solution infusion (the control group). Infusion was given a day before surgery and repeated four hours before starting extracorporeal circulation (CPB) via the pe ripheral vein at single doses of 100 mL (25 mL/h). Platelet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Fish oil has been shown to reduce stimulated platelet aggregation and increase bleeding time. 12,13 In a recent study, Gong et al. 14 showed that omega-3 fatty acids in combination with low-dose aspirin led to a significant reduction in platelet aggregation as measured with Born aggregometry in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Fish oil has been shown to reduce stimulated platelet aggregation and increase bleeding time. 12,13 In a recent study, Gong et al. 14 showed that omega-3 fatty acids in combination with low-dose aspirin led to a significant reduction in platelet aggregation as measured with Born aggregometry in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fish oil has been shown to reduce ADP-, adrenaline- and COL-induced platelet aggregation as well as P-selectin expression and to increase bleeding time [ 20 ]. Veljovic et al [ 19 ] studied intravenous administration of 2100 mg Ω-3 polyunsaturated fatty acids 1 day and 4 h prior to coronary bypass surgery in a prospective randomized controlled trial. Compared to controls, Ω-3 polyunsaturated fatty acids significantly reduced postoperative platelet aggregation measured with Multiplate COL assay.…”
Section: Discussionmentioning
confidence: 99%
“…Neither ROTEM nor TEG has been used to monitor naturopathic medicines. Fish oil has been shown to reduce platelet collagen receptor function, as detected by the Multiplate COL [ 19 ] and ADP tests [ 11 ]. A review article mentions reduction of thromboxane A2 levels as a possible mechanism of garlic and fish oil [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed no differences in international normalized ratio (INR), activated partial thromboplastin time, bleeding volume, blood transfusion or fresh frozen plasma requirements, platelet count in postoperative period, and heparin or protamine use. Only in one of four tests platelets activity was statistically lower in the FO group, but with no negative effect (50).…”
Section: Hemostasismentioning
confidence: 71%